Addressing usability quality attribute in techno-spiritual mobile application - Abdul Wahab, Ahairul Afza (2015)
Technology trending toward mobile devices provide significant medium for the growth of mobile applications. It grants users with advantages of portability and accessibility in the mobile context. Application providers seen this as new marketing opportunities to promote and sell products directly engagement with application users through mobile websites. This influence providers increase application development and productivity for target consumer application markets such as games and lifestyle category with potential of better revenues. This mobilisation creates integrating technology with spirituality content known as techno-spiritual which information technology assist in humans‘ spiritual and religious practices. Currently there is increasing numbers of provider involve translating spirituality content into new mobile application medium and reaching users through mobile websites. This helps any religious devotees such as Islam, Buddhism, Hinduism and Christianity engage with spiritual information. The techno-spiritual application focus in this paper more on Islamic Quran recitation for Muslims that used for read the Quran in Arabic alongside its translation. The popularity demand for techno-spiritual applications development address challenges and concerns for provider in term quality dimension impacting the success of products. Their expectations for quality products are high in delivering valuable content and useful functionality. It should convenient and simple for prolong the usage of applications. Usability is widely used for quality evaluation and measurement of mobile application usable. It‘s referring the capability of the application to be learned, operated, attract and satisfy users in mobile environment This study aims addressing usability quality attribute in techno-spiritual mobile application which beneficial practitioners in design and develop usable mobile applications in the future.